Accountability Dysfunction in Campaign Finance Regulations: A Case Study of the 2018 Jambi Simultaneous General Elections (Jurnal Bina Praja, 2020)
The regulations of campaign finance have highly problematic for local electios (Pilkada) in Indonesia. However, the campaign finance system changed gradually over the following years, many alleged campaign violations committed by candidates during local elections. In this study, the researcher wants to assess campaign finance regulations based on the accountability concept. The measurement of accountability in the campaign finance regulations has been divided into two perspectives, which are legal and finance. The study used a qualitative method with a case study approach in Jambi's three regions, which held local elections (Pilkada) in 2018. This study argues that the current regulations have not solved the whole problem of campaign funds. The level of corruption by candidates remains stubbornly high due to less authority and weak sanctions. At the same time, most campaign finance regulations have never been enforced. As a result, revising Acts on the election, enhancing law enforcement, and raising public awareness need to promote for ensuring the quality of local democracy.